(untitled) (Research, Society and Development, 2020)
The objective of this study was to describe the profile of mortality due to land transport accidents (ATT) in the state of São Paulo and the effects of Prohibition on the mortality rate. Deaths with codes V01-V89 determined in the 10th review of the International Classification of Diseases (ICD-10) were selected by the Mortality Information System (SIM), based on the ATT. It was calculated, for 8 years before and 9 years after the Law, the mortality rate due to ATT according to age group and sex. In addition to the distribution (absolute and percentage) of mortality due to ATT related to the variables: age group, sex, race, education, marital status, category of ICD-10 and by regional health departments (DRS). The results showed a tendency towards an increase in deaths due to ATT before the law and a decrease in deaths after the law, in addition to a higher frequency of mortality among males, between 20-39 years, single, white, with schooling of 4-7 years before the Law and 8-11 years after the Law. Higher mortality in the Municipalities of Greater São Paulo, Baixada Santista, Registro and Taubaté both before and after the Law; higher record of mortality from other ATTs before the law and a higher frequency of pedestrians traumatized by ATTs after the law. It is concluded that the implementation of the Prohibition Act positively interfered in the mortality rate observed in the period and in the variables analyzed.